Anti-tumor Efficacy Assessment of the Sigma Receptor Pan Modulator RC-106. A Promising Therapeutic Tool for Pancreatic Cancer - Tesei, Anna; Cortesi, Michela; Pignatta, Sara; Arienti, Chiara; Dondio, Giulio Massimo; Bigogno, Chiara; Malacrida, Alessio; Miloso, Mariarosaria; Meregalli, Cristina; Chiorazzi, Alessia; Carozzi, Valentina; Cavaletti, Guido; et al. (Frontiers in Pharmacology, 2019)
Introduction: Pancreatic cancer (PC) is one of the most lethal tumor worldwide, with no prognosis improvement over the past 20-years. The silent progressive nature of this neoplasia hampers the early diagnosis, and the surgical resection of the tumor, thus chemotherapy remains the only available therapeutic option. Sigma receptors (SRs) are a class of receptors proposed as new cancer therapeutic targets due to their over-expression in tumor cells and their involvement in cancer biology. The main localization of these receptors strongly suggests their potential role in ER unfolded protein response (ER-UPR), a condition frequently occurring in several pathological settings, including cancer. Our group has recently identified RC-106, a novel pan-SR modulator with good in vitro antiproliferative activities toward a panel of different cancer cell lines. In the present study, we investigated the in vitro properties and pharmacological profile of RC-106 in PC cell lines with the aim to identify a potential lead candidate for the treatment of this tumor. Methods: Pancreatic cancer cell lines Panc-1, Capan-1, and Capan-2 have been used in all experiments. S1R and TMEM97/S2R expression in PC cell lines was quantified by Real-Time qRT-PCR and Western Blot experiments. MTS assay was used to assess the antiproliferative effect of RC-106. The apoptotic properties of RC-106 was evaluated by TUNEL and caspase activation assays. GRP78/BiP, ATF4, and CHOP was quantified to evaluate ER-UPR. Proteasome activity was investigated by a specific fluorescent-based assay. Scratch wound healing assay was used to asses RC-106 effect on cell migration. In addition, we delineated the in vivo pharmacokinetic profile and pancreas distribution of RC-106 in male CD-1 mice. Results: Panc-1, Capan-1, and Capan-2 express both SRs. RC-106 exerts an antiproliferative and pro-apoptotic effect in all examined cell lines. Cells exposure to RC-106 induces the increase of the expression of ER-UPR related proteins, and the inhibition of proteasome activity. Moreover, RC-106 is able to decrease PC cell lines motility. The in vivo results show that RC-106 is more concentrated in pancreas than plasma. Conclusion: Overall, our data evidenced that the pan-SR modulator RC-106 is an optimal candidate for in vivo studies in animal models of PC.